Genome sequence of rheinheimera sp strain A13L, isolated from pangong lake, india - Gupta, Hemant Kumar; Gupta, Rinkoo Devi; Singh, Ajit; Chauhan, Nar Singh; Sharma, Rakesh (Journal of Bacteriology, 2011)
Rheinheimera sp. strain A13L, which has antimicrobial activity, was isolated from alkaline brackish water of the high-altitude Pangong Lake of Ladakh, India. Here we report the draft genome sequence of Rhienheimera sp. strain A13L (4,523,491 bp with a G + C content of 46.23%). The genome is predicted to contain genes for marinocine and colicin V production, which may be responsible for the antimicrobial activity of the strain.